Correlation Between Structural Features and Magnetic Performance of Fe93.5Si6.5 (wt.%) Soft Magnetic Materials - Yang, Jing; Fu, Zongwen; Wahl, Larissa; Travitzky, Nahum; Körner, Carolin (Advanced Functional Materials, 2023)
Laminated, powder filled, and dense bulk soft magnets are currently used for various electrical and electronic applications due to their characteristic magnetic properties. In order to systematically investigate the correlation between the structural features and the resulting magnetic performance of various soft magnetic materials, toroidal Fe93.5Si6.5 (wt.%) specimens with “layer structure”, “powder structure”, and “dense structure” are additively manufactured and characterized by means of electron beam powder bed fusion (PBF-EB). The specimens with “layer structure” show outstanding magnetic performance in terms of low power losses and good maximum magnetic flux density at frequencies ranging from 50 to 1000 Hz, outperforming even some soft magnetic materials fabricated using conventional methods. Fe93.5Si6.5 (wt.%) specimens with various layered structures are produced using different processing strategies, allowing for sophisticated structural tailoring, and modifying the corresponding magnetic performance. Based on the results derived in this study, an ideal structure that can result in superior soft magnetic properties is proposed.
CRIS-Team Scopus Importer:2023-12-15
Keywords: electron beam powder bed fusion (PBF-EB); Fe; magnetic flux density; power losses; structural features

Electron beam-based additive manufacturing of Fe93.5Si6.5 (wt.%) soft magnetic material with controllable magnetic performance - Yang, Jing; Fu, Zongwen; Ye, Jihui; Kübrich, Daniel; Körner, Carolin (Scripta Materialia, 2022)
Crack-free Fe-Si soft magnetic material with various microstructural features is additively manufactured by means of Electron beam Powder Bed Fusion (E-PBF). Owing to different microstructural features caused by using different processing parameters, E-PBF-processed Fe93.5Si6.5 (wt.%) shows adjustable magnetic performance (e.g., power losses and saturation magnetic flux density) and various electrical properties. The correlation between the processing parameters used during E-PBF and the corresponding microstructural features as well as the resulting magnetic and electrical properties is discussed.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Electron beam Powder Bed Fusion; Fe-Si soft magnetic material; Magnetic properties; Microstructure

Electron beam-based additive manufacturing of Fe-Si soft magnetic materials - Yang, Jing (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)

Structure Design of Soft Magnetic Materials using Electron Beam‐based Additive Manufacturing - Yang, Jing; Fu, Zongwen; Körner, Carolin (Advanced Materials, 2023)
Fe93.5Si6.5 (wt.%) soft magnetic materials in toroidal shape are additively manufactured by means of Electron Beam Powder Bed Fusion (PBF-EB). Different hatching strategies are applied to realize specific patterns of molten material alternating with non-molten powder particles. The specimens produced using different hatching strategies show identical relative densities but various structural features resulting in different magnetic properties. The magnetic performance of the specimens is characterized by determining hysteresis loops (B-H curves), power losses and maximum magnetic flux density at frequencies between 50 Hz and 1000 Hz. At constant mass, the different structures induced by using various hatching strategies have a strong influence on the hysteresis losses. These losses can be significantly reduced by applying a targeted structure design. The modified specimens show superior magnetic properties at sub-kHz compared to some soft magnetic materials fabricated by means of conventional methods and Laser Powder Bed Fusion (PBF-L).<br